(Z)-3-Hydrazinylidene-1-phenylindolin-2-one - Abdel-Aziz, H.A.; Bari, A.; Aboul-Fadl, T.; Ng, S.W. (International Union of Crystallography, 2010)
The indoline fused-ring system of the title Schiff base, C14H11N3O, is planar (r.m.s. deviation = 0.005 angstrom); the phenyl substituent is aligned at 66.5 (1)degrees with respect to the ring system. The amino -NH2 unit forms an intramolecular hydrogen bond with the carbonyl O atom. Molecules are connected by an intermolecular N-H center dot center dot center dot N hydrogen bond, generating a zigzag chain that runs along the short c axis of the unit cell.